Adult Obesity Prevalence in Public Institutions in Mersin Province - Volkan Recai Ötegen; Tufan Nayir; Muhsin Akbaba; Ersin Nazlıcan (Sakarya Tıp Dergisi, 2018)
Objective: The aim of this study is to reflect the latest information about obesity frequencies and involving factors in Mersin province, Turkey. Methods: A total of 8272 people were included in the study. Body mass index was obtained from the formula by proportioning body weight to the square of the height in meters ( weight / height2, kg / m2). Socio-demographic characteristics, physical activity, nutrition habits related questions have been applied under the 26-question survey to the staff who agreed to participate. Results: 3872 of the respondents (47.52%) were women, 4277 (52.48%) were male. The mean age of the participants was 39.09, the lowest age of 16, the highest was 65. Both age and sex effects adult obesity prevelance. %48.05 of participants was overweight and